2012
DOI: 10.4236/cellbio.2012.11002
|View full text |Cite
|
Sign up to set email alerts
|

Micromorphology and Ultrastructure of the Foot of the Equilateral Venus <i>Gomphina veneriformis</i> (Bivalvia: Veneridae)

Abstract: The shape and microscopic structure of the foot of the equilateral Venus, Gomphina veneriformis are described by light and electron microscopy along with the substrate conditions of their habitat. The habitat sediment of G. veneriformis is composed of sand (2-0.063 mm in diameter), mainly. The foot is wedge-shaped with multiple vertical furrows on the surface. Although the foot is composed of an epithelial layer, a connective tissue layer and a muscular layer, the boundary between the connective tissue and mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…5a). Park et al (2012) revealed similar observations in feet musculature of equilateral bivalves Gomphina Veneriformis. The muscle fibres as a whole showed integrity and proper structure with no signs of splitting fibres.…”
Section: Feetsupporting
confidence: 74%
“…5a). Park et al (2012) revealed similar observations in feet musculature of equilateral bivalves Gomphina Veneriformis. The muscle fibres as a whole showed integrity and proper structure with no signs of splitting fibres.…”
Section: Feetsupporting
confidence: 74%